Pendampingan Dan Sosialisasi Pengolahan Limbah Diapers Sebagai Alternatif Media Tanam Dan Pupuk - Perangin-angin, Susanti Br; Manik, Erba Kalto; Tanjung, Nelson (Journal of Smart Community Service, 2023)
AbstractIndonesia is the third largest consumer of disposable baby diapers after India and China. Research conducted on babies aged 0-2 years, this research was conducted by Ritcer in 2005. The use of disposable diapers in Indonesia can reach around 12 million disposable diapers every year. Based on a study by Sigma Research (2017), it was found that the highest initial use of diapers in babies aged two years was between the ages of 0-3 months, namely in babies aged < 1 month it was 16.1%, and the highest was obtained when babies were aged 1 - 3 month amounted to 69.6%. Disposable baby diapers are the most popular among mothers with a percentage of 95.2%. This type of diapers and pampers waste can actually be categorized as B3 waste because of its infectious nature, but in fact not many people in the field have paid attention to this problem or even prepared a disposal and management system for the general public, especially in rural areas, so it becomes a big problem if a security system is not implemented. waste that is infectious in nature. The aim of this community service activity is to understand the sources & negative impacts of diaper waste, know how to use diaper waste as a planting medium and fertilizer, know the tools and materials for making planting media and fertilizer from diaper waste, know the steps for making planting media and fertilizer from diaper waste and the practice of making planting media and fertilizer from diaper waste independently. The method of community service activities is entrepreneurship training for the community to process diaper waste into alternative planting media and fertilizer so that plants, both flowers and vegetables, grow effectively. From learning about the experiences of friends who are observers of waste and the environment in the field, there is an enlightenment and some of the experiences of someone who has applied them in the field of waste problems and who has dealt with the pampers waste problem can be imitated and hopefully it will be useful.